42 / 7 = 6
bc it is the complete opposite
It means that all values of x would make it true. Also take a look at the equation when we simplify:
4x + 7 = 1 + 4x + 6
Which simplified turns into
4x + 7 = 4x + 7
So no matter what value you put for x, it will be the same on both sides, making all values true for x.
Answer:
19.6
Step-by-step explanation:
Half it and then multiply and divide
Hi!
<u>Given these two equations:</u>
![x = y + 8](https://tex.z-dn.net/?f=x%20%3D%20y%20%2B%208)
![x + 4 = 2(y + 4)](https://tex.z-dn.net/?f=x%20%2B%204%20%3D%202%28y%20%2B%204%29)
We want to solve using the substitution method. Knowing that x is equal to y + 8, we can simply plug in 'y + 8' in for x in the second equation, like so:
![(y+8)+4=2(y+4)](https://tex.z-dn.net/?f=%28y%2B8%29%2B4%3D2%28y%2B4%29)
Combine like terms on both sides:
![y+12=2y+8](https://tex.z-dn.net/?f=y%2B12%3D2y%2B8)
Subtract y from both sides:
![12=y+8](https://tex.z-dn.net/?f=12%3Dy%2B8)
Subtract 8 from both sides:
![y=4](https://tex.z-dn.net/?f=y%3D4)
Now, we can simply plug the y value in to the first equation, and solve for x:
![x=4+8](https://tex.z-dn.net/?f=x%3D4%2B8)
Simplify:
![x=12](https://tex.z-dn.net/?f=x%3D12)
<h3>
Therefore, x is equal to 12 and y is equal to 4.</h3>
<u>Learn more about the substitution (and also elimination!) method here:</u>
brainly.com/question/14619835